Penerjemahan Metafora Bahasa Indonesia Ke Bahasa Jepang - Putri Puji Astuti; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research is intended to find out how the metaphor of Indonesiantranslated into Japanese in the novel “Cantik Itu Luka”, which has beentranslated into Japanese entitled Bi Wa Kizu. The method of this research isdescriptive. The writer analyzed the method and procedure the translator used intranslating the Indonesian metaphor into Japanese and so do the theory used increating the correspondence between the meanings of the words.Based on the study results, (1) the authors concluded that the translatoruses communicative translation method, which emphasizes the translation in thetarget language. Meanwhile, the procedure used is the procedure of changing theshape and change the meaning. (2) Metaphor senses animals on source text (TSu)is translated into three forms that is metaphor becomes general meaning,metaphor becomes metaphor with different senses, and metaphor becomesmetaphor with the same senses. (3)Metaphor senses anthropomorphic istranslated to be literal meaning. (4) Metaphor abstract to concrete is translatedinto four form that is metaphor becomes metaphor with different sense, metaphorbecomes literal meaning, metaphor is eliminated, metaphor becomes metaphorwith additional sense. (5) Synesthesia metaphor is translated to the samemetaphor.Keyword: Metaphor, Translation, Cantik Itu Luka